2010
DOI: 10.4085/1062-6050-45.2.147
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hydration on Physiological Function and Performance During Trail Running in the Heat

Abstract: Context: Authors of most field studies have not observed decrements in physiologic function and performance with increases in dehydration, although authors of well-controlled laboratory studies have consistently reported this relationship. Investigators in these field studies did not control exercise intensity, a known modulator of body core temperature.Objective: To directly examine the effect of moderate water deficit on the physiologic responses to various exercise intensities in a warm outdoor setting.Desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
126
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(134 citation statements)
references
References 43 publications
(82 reference statements)
3
126
0
5
Order By: Relevance
“…The higher the urine density, the more dehydrated the individual. A USG of less than 1.010 g/ml is well hydrated, a urine density of 1.011.020 g/ml is minimally dehydrated and a urine density of 1.021-1.030 g/ml is significant dehydration [20]. Of the seven participants, only one participant was well hydrated following a 24-hour consumption of thickened liquids, four participants had mild dehydration, and two participants had significant dehydration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The higher the urine density, the more dehydrated the individual. A USG of less than 1.010 g/ml is well hydrated, a urine density of 1.011.020 g/ml is minimally dehydrated and a urine density of 1.021-1.030 g/ml is significant dehydration [20]. Of the seven participants, only one participant was well hydrated following a 24-hour consumption of thickened liquids, four participants had mild dehydration, and two participants had significant dehydration.…”
Section: Discussionmentioning
confidence: 99%
“…Six of the participants exhibited an increase in USG following the 24 hour period of thickened liquid intake, thus indicating a decrease in hydration [20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous investigations have indicated that hypohydration can reduce exercise performance in the heat and lead to serious heatrelated illnesses [7,8]. While consumption of fluid during exercise can effectively reduce rates of dehydration, some individuals such as soldiers or endurance athletes participating in unsupported training sessions, may not have access to adequate fluid supplies and/or may have sweat rates that exceed the maximum rate of gastric emptying for water [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…1 These are generally regarded as more strenuous than road running due to the nature of the trails, which can involve diverse challenges including single track paths on steep ascends and descends in mountains, crossing rivers and running along grasslands and through forests. 2 Although physiological response to single-day trail running has been assessed, [1][2][3][4] the cumulative effects of multi-day trail running on markers of muscle damage and inflammation have not yet been reported. Prolonged endurance exercise causes muscle damage that initiates an inflammatory response and subsequent remodelling of muscle.…”
Section: Introductionmentioning
confidence: 99%